Challenges in Shariah Audit Practices from the Lense of Practitioners: The Case of Malaysian Takaful Industry - Noor Aimi Mohamad Puad, Zurina Shafii , Nurdianawati Irwani Abdullah (International Journal of Advanced Science and Technology, 2020)
Shariah audit is one of Islamic Financial Institutions’ essential functions as it provides an independent opinion of the primary purpose of the establishment of Islamic Financial Institutions as to whether or not the institutions are shariah compliant. Usually, the duties of shariah auditors will be carried out by the internal auditors of each Islamic Financial Institution. However, the effective performance of such duties would depend on the challenges faced by the auditors in conducting shariah audit exercises. Therefore, the main objective of this study is to critically examine the challenges faced by practitioners in conducting shariah audits and to provide suggestions to overcome the barriers and attain an effective shariah audit function. A series of semi-structured interviews were undertaken with key individuals in Malaysian Takaful Operators who were involved directly and indirectly in the shariah audit process. The key individuals include shariah auditors, shariah officers, and shariah committee members. The findings of the study highlight the key challenges as described by the practitioners. The study then proposes solutions to overcome the challenges. The recommendations from the study are useful in enhancing the current shariah audit practices as well as improving the shariah audit quality.